Pengalaman Adaptasi Orang dengan HIV untuk Mempertahankan Kualitas Hidup - Enggelino Awom; Ferry Agusman; Sabina Gero (Jurnal Sehat Mandiri, 2025)
HIV remains a global health problem with a prevalence of 20.8 million people in 2022, while in Indonesia 50,282 cases were reported, with Teluk Bintuni being one of the areas with high prevalence. This study aimed to explore the experiences of people living with HIV (PLHIV) in adapting to maintain their quality of life. A qualitative phenomenological approach was employed with purposive sampling of six PLHIV participants at Teluk Bintuni Regional General Hospital, conducted from September to December 2024. Data were collected through in-depth interviews, observations, and documentation, then analyzed phenomenologically. The findings revealed that most participants were aged 36–45 years, predominantly unmarried, and categorized as having early-stage HIV. Physiological adaptation was shown through adherence to antiretroviral (ARV) therapy and the adoption of a healthy lifestyle. Psychologically, participants experienced a transition from emotional stress to acceptance and gratitude, while spiritual adaptation was reflected in regular worship and strengthening faith. Socially, stigma encouraged most participants to conceal their HIV status, although family and healthcare support played a crucial role in sustaining treatment. In conclusion, the adaptation of PLHIV is multidimensional—encompassing physiological, psychological, spiritual, and social aspects—highlighting the importance of interventions to reduce stigma and strengthen community support in order to improve their quality of life.